Developed erotomania in the treatment of obsessive-compulsive disorder: A case report [Obsesif-kompulsif bozukluǧun tedavi sürecinde gelişen erotomani: Bir olgu sinumu] - (:unkn) unknown (Cukurova Univ Tip Fakultesi Psikiyatri Anabilim Dali, 2000)
The observations on the psychotic features of clinical presentation of obsessive-compulsive disorder (OCD) has been an interesting topic for most researchers. Despite the fact that our knowledge of childhood onset OCD is growing day to day, our understanding of development of delusional thought is still limited. In the present paper, a 14 year-old female adolescent who developed erotomania during the course of obsessive-compulsive disorder is discussed in the context of psychopathology and development. It is aimed to broaden our understanding of OCD and delusional disorder phenomena.
Keywords: Adolescent; Childhood; Erotomania; Obsessive-compulsive disorder